PENGARUH UKURAN PERUSAHAAN, PERTUMBUHAN PENJUALAN, KEPEMILIKAN INSTITUSIONAL TERHADAP KONDISI FINANCIAL DISTRESS PADA SEKTOR PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - admin, Tri Kurniati Khairunnisa B11112077 (Jurnal Manajemen Update, 2016)
Financial distress is one of the characteristics of companies that are being buffeted by financial problems. The problem of financial distress if not immediately addressed will end up with bankruptcy. This study aims to determine the effect of company size, sales growth, institutional ownership on financial distress in the mining sector listed on the Indonesia Stock Exchange (IDX). This research is quantitative. The data collection was obtained by collecting secondary data by using the method of study documentation and study of literature. This study uses time series data in the form of annual reports for 5 years from 2010 - 2014. Purposive sampling method is used as a method of sampling with the following criteria: 1) the companys in mining sector listed in Indonesia Stock Exchange that provides financial reports of the year 2010 - 2014, 2) the list of mining companies that use the currency of rupiah in financial reports, 3) the list of companies that have financial data that is complete in accordance with the data needed to measure the studied variables and to financial distress proxy with EPS, in order to obtain a sample of 16 companies.Â  Technique of analysis data used multiple regression analysis. Based on the research results of the research showed that company size has a negative and significant impact on the financial distress. While sales growth and institutional ownership do not have a significant effect on the financial distress. Â  Keywords: Company Size, Sales Growth, Institutional Ownership, Financial Distress.